PEMBUATAN PAPAN PARTIKEL DENGAN MENGGUNAKAN BAHAN BAKU TANDAN KOSONG KELAPA SAWIT DAN PEREKAT RESIN - Lubis, Ahmad Fahmi Alhafiz; Effendi, Zulham; Guntoro, Guntoro (Institut Teknologi Sawit Indonesia (ITSI), 2022)
Oil palm is a plantation crop that has an important role in Indonesia today. This plant is a plant that produces vegetable oil and its derivative products. The processing of oil palm empty bunches into particle board as a strategy for utilizing solid waste from oil palm processing has been carried out. The test was carried out to determine the hardness, weight and moisture content to produce particle board. The board making was carried out in April - August 2020. The location was at the Laboratory of Soil and Fertilizer at the College of Agricultural Agribusiness and Plantation (STIPAP) and the Laboratory of Industrial Chemistry Polytechnic Medan (PTKI). The results showed that the largest water content of oil palm empty fruit bunches was obtained by 44%, then for the weight of the content obtained 1.131 gr / cm3 with a ratio of 50% oil palm empty bunches fiber and 50% resin adhesive and a hardness test value of 76 kg. . The moisture content can affect the resistance and weight of the particle board so that drying is necessary. Meanwhile, the weight of the contents has an effect on particle density, thereby increasing the hardness of the material.